Clinical and endoscopic profile of the patients with upper gastrointestinal bleeding in central rural India: A hospital-based cross-sectional study - Jyoti Jain; Anoop Rawool; Shashank Banait; Chetna Maliye (Wolters Kluwer Medknow Publications, 2018)
Introduction: Acute Upper Gastrointestinal bleeding (UGIB) is one of the common causes with which the patients present to emergency. The upper gastrointestinal (UGI) endoscopy remains a crucial tool in identification of UGIB. The aim of the present study was to determine the endoscopic profile of UGIB in adult population of rural central India admitted with history of UGIB (hemetemesis and/or malena). Methods: This prospective, cross sectional study was conducted in rural hospital in central India and we enrolled all consecutive patients aged 18 years and above who were admitted in the hospital ward with the history of UGIB. After obtaining the demographic data, all patients underwent clinical examination, laboratory investigations and video-endoscopy. We used Student's t test to compare means, Chi-square test to compare proportions and Mann-Whitney test to compare medians. P value <0.05 will be considered significant. Results: The mean age of our study population (N = 118) was 46.2 years. Among 118 patients who underwent endoscopy, 47.4% had esophageal varices, 27.1% had portal hypertensive gastropathy, 14.4% had gastric erosions, 5.9% each had duodenal ulcers and esophagitis, 5% had gastric ulcer disease, 4.2% each had Mallory-Weiss tear and had gastric malignancy, 1.7% had esophageal malignancy and 16.1% had normal endoscopic findings. Conclusion: Esophageal varices were the most common cause of UGIB in the adult population of rural central India presenting with UGIB, when diagnosed by video-endoscopy.